Oil palm Empty Fruit Bunch (EFB) fiber reinforced poly(lactic) acid composites : effects of fiber treatment and impact modifier - Akindoyo, John Olabode (2015)
The use of natural fibers as reinforcement in polymer composites has become necessary based on the several advantages of lignocellulosic fibers over their inorganic counterparts. However, limitations to the use of natural fiber in composites are the inherent reduced adhesion between the fiber and matrix, high moisture absorption and UV degradation owing to non-cellulosic components of natural fibers. In this research, composites were fabricated from oil palm empty fruit bunch fiber (EFB) and poly lactic acid (PLA) with different loading percent of 10-40 wt%. Mechanical testing revealed that 30 wt% of fiber content produced the highest mechanical properties and this was selected as the optimum fiber content based on treated EFB fiber that were fabricated. To enhance the compatibility of EFB with PLA, the fiber surface was treated by ultrasound in both water and alkali medium and optimization was done by response surface methodology (RSM), which selected 100 mins exposure time at 90oC in 2 wt% NaOH as the optimum treatment condition. Fibers were further treated with poly(dimethysiloxane) coupling agent to increase bonding of EFB with PLA. Effects of fiber treatment were investigated through mechanical, structural, morphological and thermal analysis. Characteristic strength analysis of fibers was also done by Weibull characteristic model. Fabrication of composites was done by extrusion followed by pelletizing after which test samples were prepared using injection moulding machine, and composite characterization was carried out. Furthermore, biostrong impact modifier was incorporated into the composites up to 2 wt% to improve the impact properties and it was found to increase the IS of PLA by 38%, but also led to reduction in other mechanical properties of EFB/PLA composites. Morphological analysis of composites fractured surface by scanning electron microscopy (SEM) and functional groups analysis by Fourier transforms infrared spectroscopy (FTIR) revealed improved adhesion of treated fibers with PLA. Structural analysis by X-ray diffraction (XRD), supported results from differential scanning calorimetric (DSC) analysis which showed that composites prepared with the combination of ultrasound alkali and silane treated fibers has the highest crystallinity index (CrI% = 75.44%). Thermogrvimetric analysis (TGA) also showed that silane ultrasound and alkali treatment of EFB fibers increased the thermal stability of the composites by raising the peak decomposition temperature, with an increase of 43% in activation energy (Ea = 56.52 kJ/mol). Natural degradation analysis also confirmed the reduced effect of environmental factors on silane and ultrasound treated fiber based composites compared to untreated fiber based composites. Besides that, water uptake analysis and contact angle measurements revealed the increased hydrophobicity of composites after silane treatment of EFB fibers, with about 106o contact angle value and less than 5% water uptake after 150 days soaking period. The highest mechanical properties were obtained from composites based on combined ultrasound, alkali and silane treated fibers